2022
DOI: 10.2169/internalmedicine.9266-21
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin-related Portal Hypertension Complicated with Esophageal Varices and Refractory Massive Ascites

Abstract: Oxaliplatin, widely used as a chemotherapy drug for colorectal cancer, is known to cause various adverse reactions. In particular, special attention for the development of portal hypertension associated with portosinusoidal vascular disease is necessary, as it is a serious adverse life-threating reaction, although rare. We herein report a case of oxaliplatin-related portal hypertension that developed several years after oxaliplatin administration and led to esophageal varices and refractory massive ascites. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…More recently, research has found that a lot of patients who received chemotherapy, and especially oxaliplatin, developed portal hypertension as part of the “porto-sinusoidal vascular disease” (PSVD). This term, proposed by the Vascular Liver Disease Interest Group, defines all the vascular liver diseases characterized by portal hypertension in absence of cirrhosis and other causes of liver disease [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, research has found that a lot of patients who received chemotherapy, and especially oxaliplatin, developed portal hypertension as part of the “porto-sinusoidal vascular disease” (PSVD). This term, proposed by the Vascular Liver Disease Interest Group, defines all the vascular liver diseases characterized by portal hypertension in absence of cirrhosis and other causes of liver disease [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although its curative effect is significant, the accompanying adverse reactions cannot be ignored. Cases of ascites induced by oxaliplatin have been reported in the past, but have been mainly attributed to complications of oxaliplatin-induced cirrhosis ( 5 , 6 ). The occurrence of ascites may be misdiagnosed as tumor recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%